Determination of aluminum induced programmed cell death characterized by DNA fragmentation in Gramineae species - VARDAR, FİLİZ; AYDİN, YILDIZ (FIRENZE UNIV PRESS, 2016)
Aluminum (Al) toxicity is one of the major abiotic stress factors that decreases crop yield in acidic soils. Al inhibits the root growth and development due to cellular toxicity including nucleus, chromosome and DNA alterations. Although some Al-induced programmed cell death (PCD) features were identified, there are limited comparative and time-dependent studies. The aim of this study is to compare the Al-induced time-dependent DNA fragmentation, the most widely evaluated criterion for PCD in six agronomic plant (maize, wheat, triticale, rye, barley and oat) roots concerning their Al tolerance. Roots were exposed to 100 mu M AlCl3 solution (pH 4.5) for different times (1/2, 1, 2, 3, 4, 5, 6, 7, 8 h). All genomic DNA was isolated from control and AlCl3 treated roots. Isolated DNA samples were analyzed by electrophoretically and DNA fragmentation was observed in triticale, rye, barley and oat roots, but not in maize and wheat. The obtained DNA fragmentation shows that wheat and maize are more tolerant than triticale, rye, barley and oat in which the PCD is active as early as 1/2 h after Al induction. The results obtained can provide a better understanding into the Al induced PCD and Al tolerance in plants.
Keywords: Aluminum toxicity; aluminum tolerance; DNA fragmentation; Gramineae; programmed cell death; ROOT-GROWTH; ACID SOILS; TOXICITY; MECHANISMS; TOLERANCE; RESPONSES; PHYTOTOXICITY; AERENCHYMA; SENESCENCE; RESISTANCE